Association between regional heterogeneity in the mid‐facial bone micro‐architecture and increased fragility along Le Fort lines. Issue 4 (24th April 2017) - Janovic, Aleksa; Milovanovic, Petar; Hahn, Michael; Rakocevic, Zoran; Amling, Michael; Busse, Bjoern; Dimitrijevic, Milovan; Djuric, Marija
Abstract: Background/Aim: Le Fort lines have traditionally been considered as zones of weakness in the mid‐facial skeleton although the structural basis of increased bone fragility at these sites has not yet been investigated. Considering recent findings of occlusal loading‐related regional heterogeneity in the mid‐facial bone micro‐architecture, the aim of this study was to explore whether such heterogeneity in cortical and cancellous bone micro‐architecture may contribute to increased fragility at Le Fort fracture sites. Materials and Methods: Twenty‐five cortical and thirteen cancellous bone specimens were harvested from a dry skull and analyzed by micro‐CT. Specimens were classified into Le Fort or Non‐Le Fort groups based on their location in the mid‐facial skeleton. Results: Cortical bone along Le Fort lines showed tendencies toward lower thickness (1.5±0.63 vs 1.75±0.79; P =.39) and greater porosity (11.48±5.67 vs 10.28±5.28; P =.59). A significant difference was detected in the trabecular degree of anisotropy which was higher in cancellous bone from Le Fort fracture sites (2.14±0.69 vs 1.58±0.34; P =.02). Conclusions: Regional heterogeneity in cortical bone micro‐architecture could not fully explain increased fragility of the mid‐facial skeleton at the Le Fort lines. However, regional differences in trabecular bone anisotropy may contribute to increased bone fragility.